2015
DOI: 10.1103/physrevd.92.071502
|View full text |Cite
|
Sign up to set email alerts
|

How to reveal the exotic nature of thePc(4450)

Abstract: The LHCb Collaboration announced two pentaquark-like structures in the J/ψ p invariant mass distribution. We show that the current information on the narrow structure at 4.45 GeV is compatible with kinematical effects of the rescattering from χc1 p to J/ψ p: First, it is located exactly at the χc1 p threshold. Second, the mass of the four-star well-established Λ(1890) is such that a leading Landau singularity from a triangle diagram can coincidentally appear at the χc1 p threshold, and third, there is a narrow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
268
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 279 publications
(274 citation statements)
references
References 81 publications
6
268
0
Order By: Relevance
“…The corresponding triangle singularity is close to the χ c1 p threshold, which can produce a threshold enhancement. Thus, they concluded that the P + c (4450) can also be the kinematical effects around the χ c1 p threshold [397]. Later, Liu et al also investigated the possibility of the P c (4450) as kinematical effects [399] and considered three typical decay mechanisms which include (a) Λ b → Λ * χ cJ → K − pJ/ψ via exchanging a proton which is the same as one of the mechanisms proposed in Ref.…”
Section: Kinematical Effectmentioning
confidence: 99%
See 4 more Smart Citations
“…The corresponding triangle singularity is close to the χ c1 p threshold, which can produce a threshold enhancement. Thus, they concluded that the P + c (4450) can also be the kinematical effects around the χ c1 p threshold [397]. Later, Liu et al also investigated the possibility of the P c (4450) as kinematical effects [399] and considered three typical decay mechanisms which include (a) Λ b → Λ * χ cJ → K − pJ/ψ via exchanging a proton which is the same as one of the mechanisms proposed in Ref.…”
Section: Kinematical Effectmentioning
confidence: 99%
“…Later, Liu et al also investigated the possibility of the P c (4450) as kinematical effects [399] and considered three typical decay mechanisms which include (a) Λ b → Λ * χ cJ → K − pJ/ψ via exchanging a proton which is the same as one of the mechanisms proposed in Ref. [397]…”
Section: Kinematical Effectmentioning
confidence: 99%
See 3 more Smart Citations